2022
DOI: 10.3390/ma15217453
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bond–Slip Laws on the Debonding Failure and Behavior of Flexural Strengthened RC Slabs in Hybrid FRP Retrofit Systems

Abstract: The hybrid retrofit system using FRP and concrete overlay applied on the top of slabs has proven effective in strengthening and overcoming logistical constraints, compared with conventional strengthening techniques using externally bonded composite materials to the underside of the slabs. Nevertheless, the performance of retrofitted slabs is governed by debonding failure due to the low bond strength between CFRP and concrete overlay. Thus, this study investigates the behavior of flexural strengthened slabs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In this study, the prediction of flexural and shear carrying capacities of strengthening slabs with retrofit systems is shown to be in good agreement with the previous literature [ 28 , 29 , 30 , 31 ]. Additionally, civil engineers, especially the authors mentioned in this topic, have also long been interested in optimizing the strength of materials for more efficient workability of structures, resulting in cutting construction costs.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, the prediction of flexural and shear carrying capacities of strengthening slabs with retrofit systems is shown to be in good agreement with the previous literature [ 28 , 29 , 30 , 31 ]. Additionally, civil engineers, especially the authors mentioned in this topic, have also long been interested in optimizing the strength of materials for more efficient workability of structures, resulting in cutting construction costs.…”
Section: Resultssupporting
confidence: 89%
“…With a focus on overcoming the drawbacks of typical strengthening techniques, an innovative hybrid retrofit system using CFRP with HPC overlay on the top surface of the existing RC slab was developed, instead of taking advantage of the high tensile strength of CFRP, as shown in Figure 1 . Previous studies have confirmed the efficiency of retrofit systems in improving strength and ductility, along with overcoming logistical challenges without complex engineering requirements [ 21 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The proposed approach has contributed to simplifying a complex issue that prevents the sudden failure of strengthened continuous structures using external bonded FRP materials. Previous studies have demonstrated a positive effect on strengthened slabs using FRP-HPC retrofit systems [ 15 , 18 , 21 ]. We can derive the failure limits for each region of the end span from the expressions below: …”
Section: Overview Theory and Proposed Processmentioning
confidence: 99%
“…The retrofitting mechanism of strengthened slabs using retrofit systems based on ACI 440.2R [ 17 ] was proposed and validated with experimental data. Nevertheless, one of the primary reasons retrofitted slabs failed to achieve their ultimate carrying capacity was a premature debonding failure between CFRP and overlay interface [ 18 ]. A specialized adhesive layer permits interfacial stress to be transferred from slab to CFRP or vice versa more effectively than from CFRP to overlay concrete, resulting in a higher potential debonding failure between overlay and CFRP [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%